Incidence of and associated factors for bacterial colonization of intravenous catheters removed from dogs in response to clinical complications - Guzmán Ramos, Pedro José; Fernández Pérez, Cristina; Ayllón Santiago, Tania; Baquero Artigao, María Rosario; Ortiz Díez, Gustavo (My University, 2017)
Background: Infection rate associated with intravenous (IV) catheter placement is emerging as an important issue in small animal veterinary medicine, mostly because of the economic costs associated with these infections. Identification of possible associated factors may provide useful information for the surveillance and prevention of such infections. Objectives: To determine the incidence of positive bacterial cultures obtained from IV catheters used in dogs hospitalized for at least 48 hours and removed because of clinical complication. To identify the bacteria involved and factors associated with bacterial colonization. Animals: One-hundred eighty-two dogs that underwent IV catheterization from January 2015 to July 2015 at the Veterinary Teaching Hospital of Alfonso X el Sabio University of Madrid were enrolled in the study. Results: The bacterial colonization rate of all IV catheters removed in response to clinical complications was 39.6%, the cumulative proportion of catheters that remained in place at 24, 48, and 72 hours after placement was 89.5, 78, and 59.4%, respectively. Multivariable Cox proportional hazards regression indicated significant associations for staff who performed catheterization (junior, P 5 .002; student, P 5 .034) and use of steroidal anti-inflammatory drugs (P 5 .036). The most frequently isolated bacterium was Acinetobacter spp. (21.7%). Conclusions and Clinical Importance: The bacterial colonization incidence related to IV catheter placement was slightly higher than the incidence described in other veterinary studies. Associated factors not previously described in veterinary medicine were found. The most frequently isolated organism was Acinetobacter spp., indicating its importance as an emerging pathogen in catheter colonization. KEYWORDS catheterization, microorganism, nosocomial, pathogen